Enzyme-Linked Immunosorbent Assay for Detection of Infectious Bronchitis Antibody in Chickens Using Local Isolate of PTS III - Indriani, Risa; Indi Dharmayanti, NLP. (JURNAL BIOLOGI INDONESIA, 2013)
An indirect enzyme-linked immunosorbent assay (ELISA) was developed for screening of antibody to avian infectiousbronchitis (IBV). Antigen was prepared from whole virus of infectious bronchitis local isolate PTS-III serotype.Optimum dilution with minimum background for antigen concentration, rabbit anti-chicken conjugate and sera indeveloped ELISA were determined 0.4ÃÂ¼g/well, 1:2000 and 1:100, respectively. Correlation optical densities (OD)were compared with a standard commercial ELISA (R2=0.933). The developed ELISA has a better sensitivity to hemagglutinationinhibition (HI) test. The developed local isolate ELISA can be used to detect antibody against infectiousbronchitis virus and it is suitable for sample screening at the diagnostic laboratories.Keywords: ELISA, antibody, chicken, IB PTS-III local isolate